Influence of Duration of a Moderate Low Temperature Storage on RNA of Cattle Diarrhea Virus Strains - Stegniy, M. Yu.; Goltsev, A. N.; Stegniy, B. T. (Problems of Cryobiology and Cryomedicine, 2006)
There was studied the effect of storage duration under conditions of moderate low temperature (from –18 down to –30°C) on the possibility to change nucleotide sequence of their genome. Analysis of obtained results testify to the fact that within the most conservative site (15’-untranslated region) of cattle diarrhea virus genome the nucleotide sequences are not impaired both in case of virus storage at temperatures from –18 down to –30°C for 13 months and under longer storage term (for 12 years). In reaction with outer primers there was impossible to reveal the products of polymerase chain reaction and when using inner primers with the length of 195 pairs of nucleotides they were obtained, that confirmed the RNA degradation during storage of moderate low temperatures.